Dual-Incision Distal Biceps Repair Using Transosseous Technique and Cortical Fixation Button - Pratya Jaratjitwilai, M.D.; Cholawish Chanlalit, M.D.; Chidchanok Sakdapanichkul, M.D. (Arthroscopy Techniques)
Complete tears of the distal biceps have been repaired with various techniques, including dual or single-incision techniques and different types of fixation. A dual incision provides an anatomic footprint and a low risk of nerve complications. A transosseous suture technique alone is usually used in a dual incision. This technical note describes fixation of the distal biceps using double methods of fixation in a cadaver: cortical button and transosseous. This double-fixation technique is suitable for both primary surgery and revision surgery. The cortical button can also prevent bone cut-through in patients with osteopenia or when tuberoplasty is required.